Art therapy - Edwards, David G. (Creative therapies in practice.)
"Brings theory to life through case material and examples of real artwork produced during therapy sessions. Practising art therapist Dave Edwards explains key theoretical ideas - such as symbolism, play, transference and interpretation - and shows how these relate to practice."--